Stable Molybdenum Oxide Cathodes: Achieving Stable Molybdenum Oxide Cathodes for Aqueous Zinc‐Ion Batteries in Water‐in‐Salt Electrolyte (Adv. Mater. Interfaces 9/2021). Issue 9 (7th May 2021) - Wang, Lei; Yan, Shan; Quilty, Calvin D.; Kuang, Jason; Dunkin, Mikaela R.; Ehrlich, Steven N.; Ma, Lu; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Marschilok, Amy C.
Abstract : In article number 2002080, Lei Wang, Amy C. Marschilok, and co‐workers report that a zinc chloride water‐in‐salt electrolyte is utilized for the first time to significantly increase the stability of an aqueous zinc/molybdenum oxide battery by forming a special surface layer protecting the zinc anode surface from dissolved molybdenum species and hydrogen gas evolution.